Antimalarial Activities of Various 4-Quinolinemethanols with Special Attention to WR-142,490 (Mefloquine) - Schmidt, L. H. (1978)
Pilot appraisals of the activities of a selected group of 4-quinolinemethanols against acute Plasmodium falciparum infections in owl monkeys indicated that compounds of this class are equally active against infections with chloroquine-resistant and chloroquine-susceptible strains and that this efficacy is not compromised by concomitant resistance to pyrimethamine, and in addition, identified three derivatives with outstanding activity (WR-226,253; WR-142,490; and WR-184,806). WR-142,490, the second 4-quinolinemethanol evaluated in the above model, was five times as active as chloroquine against infections with the chloroquine-susceptible, pyrimethamine-resistant strain and had a much larger therapeutic index. Expanded evaluations designed to support projected studies in human volunteers provided full confirmation of the pilot appraisals and in addition showed: (i) that the activity of WR-142,490 was a function of the total dose delivered, single doses being as effective as three or seven fractional doses administered over as many days; (ii) that intravenous administration of this agent was feasible and effective; and (iii) that the compound was at least as active against infections with P. vivax as against infections with P. falciparum. Companion studies in rhesus monkeys infected with P. cynomolgi showed that WR-142,490 lacked prophylactic or radical curative activity, but that it was as effective as chloroquine as a companion to primaquine in a combination curative drug regimen. The results of human volunteer and field trials agree well with comparable segments of these experimental evaluations.